IDENTIFIKASI POSSIBLE SARCOPENIA MELALUI TES CALF CIRCUMFERENCE PADA AKTIVITAS FISIK USIA REMAJA - Roro Shinta Arisanti, Raden; Natalia Yuwono; Erik Jaya Gunawan (Jurnal Kesehatan dan Pembangunan, 2025)
Physical activity is a movement activity that involves the physical through elements of the limbs in the form of muscles, small muscles or large muscles. Sarcopenia is a progressive decrease in muscle mass and strength, which usually occurs during aging, is a syndrome that is directly influenced by physical activity. Measurement of muscle strength and measurement of physical performance as additional methods to diagnose sarcopenia. Calf circumference is a measurement test to see the circumference of the calf. This study is a quantitative study. The samples used were students from West Surabaya High School and students from the Ciputra Faculty of Medicine, with details of 40 students with an age range between 14-16 years and 67 students with an age range between 17-23 years. The results of the study that have been obtained were obtained from 67 students, 14 men with a percentage of 21% were categorized as normal, while 8 men with a percentage of 12% were categorized as possible sarcopenia. Of the 67 people, 27 women with a percentage of 40% were categorized as normal, while 18 women with a percentage of 27% were categorized as possible sarcopenia. While of the 40 students, 20 men with a percentage of 50% were categorized as normal, while 9 men with a percentage of 23% were categorized as possible sarcopenia. Of the 40 people, 6 women with a percentage of 15% were categorized as normal, while 5 women with a percentage of 13% were categorized as possible sarcopenia.